PENINGKATAN HASIL BELAJAR IPA PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN MAKE A MATCH PADA KELAS 4 SD - Wahyu Tri Raharjo; Firosalia Kristin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2019)
This study aims to determine the steps to implement the Make a Match learning model and improve learning result sains through the application of the Make a Match learning model to Grade IV students of Kutowinangun State Elementary School 04 Salatiga. This type of research is Classroom Action Research (PTK) with research subjects in 4th grade students of Kutowinangun State Elementary School 04 Salatiga consisting of 13 male students and 15 female students. The data collection technique used is test. The procedure of action research consists of two cycles. Each cycle through four stages of research includes: planning, action, observation, and reflection. The data analysis technique used was quantitative descriptive and qualitative descriptive. The percentage of completeness of learning result showed that in pre-action as many as 4 students completed (14%), increased to 16 students completed (57%) in the first cycle, and increased to 26 students completed (93%) in second cycle. From this data it can be conclude through the application of the Make a Match learning model can improve the learning resulth sains of 4th grade students of Kutowinangun State Elementary School 04 Salatiga.